Palladium-catalyzed chain-growth polycondensation of AB-type monomers: High catalyst turnover and polymerization rates - Tkachov, Roman; Senkovskyy, Volodymyr; Beryozkina, Tetyana; Boyko, Kseniya; Bakulev, Vasiliy; Lederer, Albena; Sahre, Karin; Voit, Brigitte; Kiriy, Anton (Angewandte Chemie International Edition, 2014)
Chain-growth catalyst-transfer polycondensations of AB-type monomers is a new and rapidly developing tool for the preparation of well-defined π-conjugated (semiconducting) polymers for various optoelectronic applications. Herein, we report the Pd/PtBu3-catalyzed Negishi chain-growth polycondensation of AB-type monomers, which proceeds with unprecedented TONs of above 100 000 and TOFs of up to 280 s-1. In contrast, related AA/BB-type step-growth polycondensation proceeds with two orders of magnitude lower TONs and TOFs. A similar trend was observed in Suzuki-type polycondensation. The key impact of the intramolecular (vs. intermolecular) catalyst-transfer process on both polymerization kinetics and catalyst lifetime has been revealed. Kicking it into high gear: Pd/PtBu 3-catalyzed Negishi chain-growth polycondensation of AB-type monomers into semiconducting polymers proceeds with unprecedented TONs as high as 100 000 and turnover frequencies of up to 280 s-1. In contrast, related AA/BB-type step-growth polycondensation proceeds with two orders of magnitude lower TONs and TOFs. Similar trends were observed in Suzuki polycondensation. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: chain growth; conjugated polymers; homogeneous catalysis; palladium; polycondensation